2020
DOI: 10.3390/nano10091772
|View full text |Cite
|
Sign up to set email alerts
|

Sono-Assembly of the [Arg-Phe]4 Octapeptide into Biofunctional Nanoparticles

Abstract: High-frequency ultrasound treatment is found to be a one-pot green technique to produce peptide-based nanostructures by ultrasound assisted self-assembly of oligopeptides. [Arg-Phe]4 octapeptides, consisting of alternating arginine (Arg/R) and phenylalanine (Phe/F) sequences, were subjected to 430 kHz ultrasound in aqueous solution in the absence of any external agents, to form [RF]4 nanoparticles ([RF]4-NPs), ~220 nm in diameter. A comprehensive analysis of the obtained nanoparticles demonstrated that the aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Their investigation confirmed that the octapeptide tends to form interconnected nanofibrillar structures rich in β-sheet structures, as well as other oligomeric species, by self-assembly via the solid-vapor phase method. Baral et al 51 recently reported that high-frequency ultrasound can be used to control the crosslinking and self-assembly processes of the [RF] 4 octapeptide ( Fig. 5a ) to form well-defined fluorescent nanoparticles ([RF] 4 –NPs), ∼220 nm in diameter with ξ potential of +39 ± 6 mV ( Fig.…”
Section: Ultrasound-driven Nanostructures From Biomoleculesmentioning
confidence: 99%
“…Their investigation confirmed that the octapeptide tends to form interconnected nanofibrillar structures rich in β-sheet structures, as well as other oligomeric species, by self-assembly via the solid-vapor phase method. Baral et al 51 recently reported that high-frequency ultrasound can be used to control the crosslinking and self-assembly processes of the [RF] 4 octapeptide ( Fig. 5a ) to form well-defined fluorescent nanoparticles ([RF] 4 –NPs), ∼220 nm in diameter with ξ potential of +39 ± 6 mV ( Fig.…”
Section: Ultrasound-driven Nanostructures From Biomoleculesmentioning
confidence: 99%
“…Recently ultrasound technology has been identified as the green technology to efficiently generate tunable multifunctional nanoparticles from biomolecules. [23][24][25][26] Most importantly, the ultrasound technique does not typically require any external toxic reagent or solvent, and can induce crosslinking of biomolecules in water, one pot and at ambient conditions. Of note, we have reported that the ultrasonic synthesis of nanoparticles is a versatile method that enables the control of nanoparticles size by regulating the acoustic power.…”
Section: Introductionmentioning
confidence: 99%
“…Bhangu et al 23,24 further exploited the mechanism for sono-responsive aromatic amino acids like phenylalanine and tryptophan to manufacture tunable multifunctional nanoparticles. Furthermore, Baral et al 26 showed that ultrasound could also influence the self-assembling of oligopeptides to fabricate well-defined biofunctional nanoparticles. In this study, we sought to apply the developed methodology to manufacture multifunctional hybrid magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The bottom-up technologies are the most widely adopted in lab-to-pilot scale applications, whereas the top-down ones may present notable advantages for industrial scale productions. However, to achieve reproducible and homogeneous nanoparticles a number of innovative process units have been developed by various researchers, taking advantage of the particular geometry and fluid-dynamic conditions established inside the specific unit [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Other technologies, green and bio-based, permit the achievement of reproducible nanomaterials, with important applications in biomedical and medical fields. In detail, Baral and co-workers [5] reported an ultra-sound assisted synthesis to produce peptidebased nanostructures [Arg-Phe] 4 octapeptides. The nanostructures consisted of alternating arginine (Arg/R) and phenylalanine (Phe/F) sequences, that were subjected to 430 kHz ultrasound in aqueous solution in the absence of any external agents.…”
mentioning
confidence: 99%